2022
DOI: 10.1063/5.0110041
|View full text |Cite
|
Sign up to set email alerts
|

Atomic diffusion in liquid Al–Cu melt under static magnetic fields

Abstract: Atomic diffusion is a natural phenomenon in liquid melt. Avoiding the melt convection is the most challenging when accuracy in measuring the diffusion coefficient of atoms is desired. The diffusion in liquid Al–Cu melts is studied under various static magnetic fields (SMFs). Thermoelectric magnetic convection is induced during the diffusion in the conductive crucible. It is suppressed by increasing the magnetic flux density or eliminated by using an insulated crucible. The interdiffusion coefficient can be acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The details of the GAAD apparatus can be found in Refs. [55,56]. Results demonstrated that the diffusionlimited condition as measured in microgravity was achieved when the MFD was greater than about 3 T. To further reveal the influence of this diffusive condition on crystal growth, Al-20wt.%Cu hypoeutectic alloy was solidified under a 24 T high SMF (Figure 3d-f) [61].…”
Section: Magnetic Braking Effect During Solidificationmentioning
confidence: 89%
See 3 more Smart Citations
“…The details of the GAAD apparatus can be found in Refs. [55,56]. Results demonstrated that the diffusionlimited condition as measured in microgravity was achieved when the MFD was greater than about 3 T. To further reveal the influence of this diffusive condition on crystal growth, Al-20wt.%Cu hypoeutectic alloy was solidified under a 24 T high SMF (Figure 3d-f) [61].…”
Section: Magnetic Braking Effect During Solidificationmentioning
confidence: 89%
“…Studies have shown that the diffusion coefficient value decreases with the increase in MFD, which provides a simulated diffusive condition [52][53][54]. Recently, a novel gravityassisted automatic docking (GAAD) device was independently developed to measure the interdiffusion coefficient of an Al-Cu alloy (D AlCu ) from 0 T to 22 T and the critical MFD for achieving the diffusion-limited condition [55,56], as shown in Figure 3a-c. The details of the GAAD apparatus can be found in Refs.…”
Section: Magnetic Braking Effect During Solidificationmentioning
confidence: 99%
See 2 more Smart Citations